HUBUNGAN PERILAKU HIDUP BERSIH DAN SEHAT DALAM TATANAN RUMAH TANGGA DENGAN KEJADIAN DIARE - Alprindo Sembiring; Friska Ernita Sitorus; Rita Ayu Butar-butar (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2020)
Diarrheal disease frequency of bowel movements more than 4 times with consistent dilute, can green or can be mixed with mucus and blood or mucus only. This study aims to determine The relationship between behavior of clean and healthy life and incidence of diarrhea at subvillage sidorame paya rumput subdistrict medan deli. The study design used is cross sectional by using total sampling method, a sample size of 50 people. Data were analyzed using chi square test, with α of 0.05. Research results obtained from 50 people who did not do a clean and healthy living behaviors there are 37 people (74%) had diarrhea, which perform a clean and healthy life behavior, there were 13 people (26%) did not have diarrhea. From the research there was no significant association of clean and healthy behaviors with the incidence of diarrhea who do not have the meaning of living a clean and healthy behaviors have a great chance of diarrhea than those who do a clean and healthy living behaviors. Suggested to the health authority health centers medan deli to take preventive action against the possible occurrence of diarrhea to reduce mortality and morbidity in diarrhea.